2017
DOI: 10.31018/jans.v9i2.1315
|View full text |Cite
|
Sign up to set email alerts
|

Performance of wool type angora rabbits under temperate conditions of Kashmir (J&K), INDIA

Abstract: An attempt has been made to determine the production and quality performance of wool type Angora rabbits and screen out the best suitable breed under temperate conditions of Kashmir. A total of 202 records of French Angora and German Angora rabbit breeds maintained for 3 years (2009)(2010)(2011) were evaluated to estimate the performance of quality and production traits in relation to genetic and non-genetic factors. For French Angora rabbits, the overall body weight gain (adult weight), annual wool yield (AWY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…The result is in accordance with the findings of Assad et al, (2017) in German Angora rabbits. However, higher (Singh et al, 2006) and lower estimates (Sood et al, 2007) of annual wool yields were also reported in German Angora rabbits.…”
Section: Annual Wool Yieldsupporting
confidence: 92%
See 1 more Smart Citation
“…The result is in accordance with the findings of Assad et al, (2017) in German Angora rabbits. However, higher (Singh et al, 2006) and lower estimates (Sood et al, 2007) of annual wool yields were also reported in German Angora rabbits.…”
Section: Annual Wool Yieldsupporting
confidence: 92%
“…Though sex was found to have non-significant effect on annual wool yield in the present study but, the wool yield of females were higher than the males (Table 2). Similar nonsignificant effects of sex on the trait were reported by Sambher et al, (1999) and Assad et al, (2017) in Angora rabbits. In contrast, Sood et al, (2007) reported significant effect of sex on annual wool yield in German Angora rabbits.…”
Section: Effect Of Year Of Birth Season Of Birth and Sex On Annual Wool Yieldsupporting
confidence: 88%
“…staple length and fiber diameter had the estimated means as 6.33 ± 0.03 cm and 13.18 ± 0.04 µ, respectively, which were in close agreement with other reports in German Angora rabbits (Ramakrishna et al 2004). However, a slightly lower estimate was reported in Angora rabbits by Assad et al 2017 andKhan et al 2020.…”
Section: Performance Traitsmentioning
confidence: 70%
“…Significant effect of sex on wool yield was also reported by Sood et al (2007). However, non-significant effect of sex on wool yield was reported by Assad et al (2017) and Sarma et al (2020) in Angora rabbits.…”
Section: Effect Of Season Of Kindlingmentioning
confidence: 85%
See 1 more Smart Citation